SARS-CoV-2 With Concurrent Respiratory Viral Infection as a Risk Factor for a Higher Level of Care in Hospitalized Pediatric Patients. Issue 9 (18th September 2022) - Dikranian, Lea; Barry, Suzanne; Ata, Ashar; Chiotos, Katie; Gist, Katja; Bhalala, Utpal; Danesh, Valerie; Heavner, Smitty; Gharpure, Varsha; Bjornstad, Erica C.; Irby, Olivia; Heneghan, Julia A.; et al.
Abstract : Objective: As of early 2021, there have been over 3.5 million pediatric cases of SARS-CoV-2, including 292 pediatric deaths in the United States. Although most pediatric patients present with mild disease, they are still at risk for developing significant morbidity requiring hospitalization and intensive care unit (ICU) level of care. This study was performed to evaluate if the presence of concurrent respiratory viral infections in pediatric patients admitted to the hospital with SARS-CoV-2 was associated with an increased rate of ICU level of care. Design: A multicenter, international, noninterventional, cross-sectional study using data provided through The Society of Critical Care Medicine Discovery Network Viral Infection and Respiratory Illness Universal Study database. Setting: The medical ward and ICU of 67 participating hospitals. Patients: Pediatric patients younger than 18 years hospitalized with SARS-CoV-2. Interventions: None. Measurements and Main Results: A total of 922 patients were included. Among these patients, 391 required ICU level care and 31 had concurrent non–SARS-CoV-2 viral coinfection. In a multivariate analysis, after accounting for age, positive blood culture, positive sputum culture, preexisting chronic medical conditions, the presence of a viral respiratory coinfection was associated with need for ICU care (odds ratio, 3.6; 95% confidence interval, 1.6–9.4; P < 0.01). Conclusions: This study demonstrates an association between concurrent SARS-CoV-2 infection with viral respiratory coinfection and the need for ICU care. Further research is needed to identify other risk factors that can be used to derive and validate a risk-stratification tool for disease severity in pediatric patients with SARS-CoV-2.